Selecting boundary conditions in physiological strain analysis of the femur: Balanced loads, inertia relief method and follower load. Issue 12 (December 2015) - Heyland, Mark; Trepczynski, Adam; Duda, Georg N.; Zehn, Manfred; Schaser, Klaus-Dieter; Märdian, Sven
Highlights: Finite element models of intact or osteotomized femur with fixation were analyzed. Boundary conditions were varied (balanced loading, inertia relief, follower load). Displacements and reaction forces depend on boundary conditions. Peak principal strains are physiological and consistent for load balanced models. The inertia relief method can be used to avoid displacement constraints. Abstract: Selection of boundary constraints may influence amount and distribution of loads. The purpose of this study is to analyze the potential of inertia relief and follower load to maintain the effects of musculoskeletal loads even under large deflections in patient specific finite element models of intact or fractured bone compared to empiric boundary constraints which have been shown to lead to physiological displacements and surface strains. The goal is to elucidate the use of boundary conditions in strain analyses of bones. Finite element models of the intact femur and a model of clinically relevant fracture stabilization by locking plate fixation were analyzed with normal walking loading conditions for different boundary conditions, specifically re-balanced loading, inertia relief and follower load. Peak principal cortex surface strains for different boundary conditions are consistent (maximum deviation 13.7%) except for inertia relief without force balancing (maximum deviation 108.4%). Influence of follower load on displacements increases with higher deflection in fracture model (from 3% to 7% for force balanced model). For load balanced models, follower load had only minor influence, though the effect increases strongly with higher deflection. Conventional constraints of fixed nodes in space should be carefully reconsidered because their type and position are challenging to justify and for their potential to introduce relevant non-physiological reaction forces. Inertia relief provides an alternative method which yields physiological strain results.